Students' Difficulties in Learning Speaking Skills at Doctor Nueng Intercare Krabi School Thailand - Najla Azkiah (Loquen, 2024)
Speaking is an essential skill that everyone needs to have to communicate with other people all around the world. The aims of this research to find difficulties in learning speaking skills at the Doctor Nueng Intercare Krabi School. Specifically for nursing students for the 2023 scholarly year, the number of students in the class is 18 people, 3 men and 15 women. This research uses a qualitative descriptive method, and in collecting data, the researcher used interviews and observation. From the results of the data that have been explained, the researcher found that there were two aspects of difficulties experienced by students, namely the linguistic aspect where students lacked vocabulary (83%), grammar (44.4%), pronunciation (50%), fluency (50%), and comprehension (44.4%). Apart from that, there are psychological aspects such as lack of confidence (44.4%), shyness (44.4%), anxiety (55.6%), and lack of motivation (61.1%). From these two aspects, the difficulties most often experienced by students are a lack of vocabulary (83%) and a lack of motivation (61.1%).